Selection of outbound locations in Gunung Kidul using a Multi- Object Optimization Method Based on Reporting Analysis - Anton Setiawan Honggowibowo; Mardiana Irawaty; Istiqomah Nuraini (Institut Teknologi Dirgantara Adisutjipto, 2020)
Decision support system (DSS) is a computer-based system that can help users make decisions. One of the DSS applications is to select outbound locations in Gunungkidul by using the Multi-Object Optimization method on the Base Ratio of Analysis (MOORA). Outbound is an open-air learning method based on direct experience presented in the form of games, discussions and adventures. So that participants will get feedback about the impact of the activities carried out which is useful for self-development in the future. The application of the MOORA method is a method that can determine the weight of each criterion, then proceed with a ranking process that will select the best alternative from a number of available alternatives. In this study an application for outbound location selection in Gunungkidul was made using the MOORA method, an application designed based on a website, this test was carried out using black box testing. The results of this study show that the best location based on the criteria weight and ranking with several alternatives is the location of the Nglanggeran Ancient Volcano with a value of 0.1507, Sri Getuk Waterfall with a result of 0.0909, Kampung Jelok with a result of 0.01497, Goa Pindul with a result of 0.00182, Sundak Beach with a result The result is -0.07192, Wulenpari with the result -0.08854, and the last one is Indrayanti beach with the result -0.13179.